Qualitative Study: Motivation, Social Aspects and Environmental Stressors in Cannabis User Patients Admitted to Abepura Regional Mental Hospital, Papua Province - Rumboirusi, Ricky Lazarus; Togodly, Arius; Medyati, Novita; Bouway, Dolfinus; Zainuri, Agus; Makaba, Sarce (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine the motivation, social aspects, and environmental stressors of cannabis-using patients treated at the Abepura Regional Mental Hospital, Papua Province. This research is a qualitative study with Collaizi's research method. The research subjects were five ethnic Papuan patients who were admitted to the Abepura Regional Mental Hospital, Papua Province. The patient population was five men with an age range of 25-39 years. The research was conducted in December 2023-January 2024. The results of the study for the motivation of marijuana users are peer influence, and seeking recognition and sensation. The results for social aspects are low economic status and poor relationships with parents. The results of the study for environmental stressors are low self-acceptance and dissatisfaction due to unmet needs at home.